IMPLEMENTASI SISTEM PAKAR DALAM MEMPREDIKSI POTENSI SIFAT BULLYING SESEORANG MENGGUNAKAN METODE FORWARD CHAINING - Sphensen Sander; Akhmad Budi (Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Technology developments are growing rapidly and give benefits in various aspects of human’s life, especially in education. The technological development in education can be used to predict bullying. This research is conducted because the society still underestimates the case of bullying, using manual way to know the potency of bullying, and some schools in Indonesia still have not given any test to predict the bullying among the students. The researcher aimed to design, construct and implement the expert system. The researcher uses system theory, experts, expert system, web, research method and bullying theory. In order to predict the potential of bullying, this research implements the forward chaining method. The data is collected by observing and interviewing counseling teacher from Santo Yoseph Senior High School, and by reading books, journals and websites as references to support this research. The researcher implements prototype model approach for this research. This Application is created in order to predict the potential of bullying in Santo Yoseph Senior High School students based on the phenomenon and calculation from the Counseling Teacher by using Forward Chaining method, and explaining the application process in the form of Use Case Diagram, use case description, sequence diagram, class diagram, entity relationship diagram and site map. The Application development is expected to be useful for Counseling Teacher in Santo Yoseph Senior High School to predict the potential of bullying among the students. Keyword : Forward chaining, bullying, expert system.